Soft‐ and reactive landing of ions onto surfaces: Concepts and applications. Issue 3 (16th April 2015) - Johnson, Grant E.; Gunaratne, Don; Laskin, Julia
Abstract : Soft‐ and reactive landing of mass‐selected ions is gaining attention as a promising approach for the precisely‐controlled preparation of materials on surfaces that are not amenable to deposition using conventional methods. A broad range of ionization sources and mass filters are available that make ion soft‐landing a versatile tool for surface modification using beams of hyperthermal (<100 eV) ions. The ability to select the mass‐to‐charge ratio of the ion, its kinetic energy and charge state, along with precise control of the size, shape, and position of the ion beam on the deposition target distinguishes ion soft landing from other surface modification techniques. Soft‐ and reactive landing have been used to prepare interfaces for practical applications as well as precisely‐defined model surfaces for fundamental investigations in chemistry, physics, and materials science. For instance, soft‐ and reactive landing have been applied to study the surface chemistry of ions isolated in the gas‐phase, prepare arrays of proteins for high‐throughput biological screening, produce novel carbon‐based and polymer materials, enrich the secondary structure of peptides and the chirality of organic molecules, immobilize electrochemically‐active proteins and organometallics on electrodes, create thin films of complex molecules, and immobilize catalytically active organometallics as well as ligated metal clusters. In addition, soft landing has enabled investigation of the size‐dependent behavior of bare metal clusters in the critical subnanometer size regime where chemical and physical properties do not scale predictably with size. The morphology, aggregation, and immobilization of larger bare metal nanoparticles, which are directly relevant to the design of catalysts as well as improved memory and electronic devices, have also been studied using ion soft landing. This review article begins in section 1 with a brief introduction to the existing applications of ion soft‐ and reactive landing. Section 2 provides an overview of the ionization sources and mass filters that have been used to date for soft landing of mass‐selected ions. A discussion of the competing processes that occur during ion deposition as well as the types of ions and surfaces that have been investigated follows in section 3. Section 4 discusses the physical phenomena that occur during and after ion soft landing, including retention and reduction of ionic charge along with factors that impact the efficiency of ion deposition. The influence of soft landing on the secondary structure and biological activity of complex ions is addressed in section 5. Lastly, an overview of the structure and mobility as well as the catalytic, optical, magnetic, and redox properties of bare ionic clusters and nanoparticles deposited onto surfaces is presented in section 6. © 2015 Wiley Periodicals, Inc. Mass Spec Rev 35:439–479, 2016.